HUBUNGAN PENGETAHUAN IBU TENTANG GIZI BALITA DENGAN STATUS GIZI BALITA BERDASARKAN BERAT BADAN / UMUR DI BIDAN PRAKTEK MANDIRI NUNIK MURTININGSIH Amd.Keb DESA PASINGGANGAN KECAMATAN BANYUMAS KABUPATEN BANYUMAS - Sintya Dwi Utami; Wilis Sukmaningtyas (Viva Medika, 2010)
Background: Many factors contribute to the problem of malnutrition may be partly due to poverty, lack of food supplies, poor environmental sanitation, including lack of publicknowledge about nutrition and health. Poor nutritional status in childhood can lead todisruption of the growth process. Due to lack of nutrition will cause some serious side effectssuch as physical growth failure, not optimal development and intelligence, decreasedproductivity, and decrease the body's resistance to disease which increases the risk ofmorbidity and mortality.Objective: To determine the relationship of nutritional knowledge of mothers about thenutritional status of children based on weight / age in MIDWIFE PRACTICES SELF NunikMurtiningsih village Amd.Keb Pasinggangan District of Banyumas Banyumas in 2012.Methods: The study design is Correlation study with cross sectional approach. Thepopulation in this study were mothers with babies in the village Pasinggangan. The samplesare saturated sample, sample of this research is all mothers with children under five in thevillage Pasinggangan Banyumas. Analysis of the data in this study is a statistical test byusing Chi-square formula (Ï‡Â²).Results: From the research, the majority of mothers about infant nutritional knowledge ispretty much as 8 respondents (40%), most of the nutritional status of children was as much as8 respondents (40%). The results of this study based on the value of the correlationcoefficient pvalue <Î± (0.010 <0.05), then Ho is rejected and Ha accepted. It can beconcluded that the strength of the relationship is strong.Conclusion: Most of the mothers in the village Pasinggangan knowledge about goodnutritional and nutritional status of children is also good. There is a relationship betweenknowledge of mothers about infant nutrition with nutritional status based on weight / agewith a strong correlation coefficient. Keywords: Toddlers Nutritional Status, Knowledge, Toddler Nutrition.